Critical communications research in Australia - Flew, Terry (Javnost (Ljubljana), 2004)
This paper tracks the development of critical communications research in Australia over a 30- year period. It assesses the relative significance of critical theory, Marxist political economy and cultural studies to the development of such a tradition, linking this to distinctive elements of Australian politics and culture, particularly the weakness of the institutional left and the significance of populism as a mode of political engagement. The paper also evaluates the rise of 'creative industries' discourse as an emergent development, and a distinctive contribution of Australian media and communications research to the field internationally.
Keywords: Australia; Avstralija; communication sciences; komunikologija; komuniciranje; communication; mass media; množični mediji; raziskave; kritična teorija